The role of clinopyroxene in generating U-series disequilibrium during mantle melting - Wood, B; Blundy, J; Robinson, J (1999)
We develop recent models of crystal-liquid partitioning (Blundy and Wood, 1994; Wood and Blundy, 1997) to predict the effects of crystal chemistry on the partitioning of U-series elements between clinopyroxene and coexisting silicate melt. With increasing pressure along the mantle solidus, clinopyroxene becomes richer in Na2O and Al2O3 and these components are predicted to reduce the size of the large M2 site. This means that, because U4+ is smaller than Th4+, clinopyroxene should progressively discriminate in favour of U4+ with increasing pressure. We find that the effect is sufficiently great that D(U)/D(Th) should change from <1.0 at pressures up to 1.0 GPa to >1.0 above 1.5 GPa. Thus, melting in the stability field of clinopyroxene should produce excess 238U relative to 230Th at low pressure and excess 230Th above 1.5 GPa. Observed excesses of 230Th in MORB may not, therefore, require the presence of garnet in the source region. We performed experiments at 1.5-1.9 GPa on compositions doped with U and Th to test the calculations. Crystals and quenched melts were analysed by ion microprobe. On the mantle solidus at 1.5 GPa, D(U)/D(Th) for clinopyroxene was found to be 1.07 ± 0.08, while a value of 1.19 ± 0.04 was obtained at 1.9 GPa. These results confirm the prediction that mantle clinopyroxenes have D(U)/D(Th) > 1.0 at high pressure. Absolute values of D(U) for clinopyroxene are 0.029 at 1.5 GPa and 0.023 at 1.9 GPa in good agreement with earlier measurements on aluminous clinopyroxenes. Corresponding values for orthopyroxene at 1.5 GPa are 1.7 X 10-3 for D(U) and 8 X 10-4 for D(Th) while olivine gave D(U) of 1.8 X 10-5 and D(Th) of 1.2 X 10-5 under similar conditions. When the new data are used in dynamic melting calculations we find that 230Th/238U activity ratios of up to about 1.23 in the liquid are consistent with melting in the spinel lherzolite field provided porosity is approximately 10-3 and melting rate ≤ 3 X 10-5 kg. m-3 yr-1. This confirms our model prediction that residual garnet is not required to generate excess 230Th in mantle melts. Solid-liquid partition coefficients for other members of the U decay series, Ra and Ac may be calculated from the model. For clinopyroxene we obtain D(Ra) of about 10-6 and D(Ac) of 5 X 10-4. The value for Ac is large enough that 227Ac activities may provide information on melt extraction processes. The M2 site of orthopyroxene is found to be elastically similar to the corresponding clinopyroxene site, which enables us to calculate for this phase, D(Ra) of 4 X 10-10 and D(Ac) of 2 X 10-6.